Sensoriamento remoto orbital como recurso para análise da ocorrência da leishmaniose tegumentar americana em localidade urbana da região Sudeste do Brasil Satellite remote sensing as a tool for the analysis of the occurrence of american cutaneous leishmaniniasis in Brazil - Cristina Miranda; Cristiano C. A. Marques; José L. Massa (Universidade de São Paulo, 1998)
INTRODUÇÃO: A ocorrência de leishmaniose tegumentar americana na região do Vale do Paraíba e litoral Norte do Estado de São Paulo foi estudada por meio de sensoriamento remoto orbital e de mapas da região. MÉTODO: As áreas consideradas de risco foram localizadas numa composição de imagens das bandas TM-3,4 e 5 do satélite Landsat, a vegetação arbustiva foi identificada e se procuraram correlações entre aquelas áreas e as características ambientais relevantes e suas mudanças. RESULTADOS: Foi caracterizada uma área de risco que pode se provar um macro habitat para vetores, reservatórios e agentes etiológicos. A busca de mudanças na paisagem e a avaliação dos dados meteorológicos não forneceram nenhum incremento dos possíveis fatores de risco. CONCLUSÕES: Existe plena correlação entre as áreas consideradas de risco e a presença de córregos e vegetação arbustiva. INTRODUCTION: The occurrence of american cutaneous leishmaniasis in the region of the Paraiba valley and the Northern shore of the State of S. Paulo, Brazil, is studied by remote sensing satellite imagery and maps of the region. METHOD: The places where infections might have occurred were plotted on a false color composition made up of Landsat TM-3,4 and 5 band images, the relevant vegetation (shrubs and trees) has been identified and correlations were sought for those areas seen as areas of risk for the disease and the environmental characteristics and their changes. The maps made it possible to add to the composite image the creeks and the contours of the tops of the large number of hills found in that region. RESULTS: An area is characterized which may prove to be a macro-habitat for vectors, reservoirs and etiological agents.The search for changes in the landscape and the evaluation of meteorological data has not yielded any possible additional risk factor. CONCLUSIONS: There is full correlation among the areas considered to present risk of infection and the presence of creeks and relevant vegetation (shrubs and trees).